The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.2134/jeq2011.0473
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Removal by Prairie Filter Strips in Row‐Cropped Ephemeral Watersheds

Abstract: Twelve small watersheds in central Iowa were used to evaluate the effectiveness of prairie filter strips (PFS) in trapping sediment from agricultural runoff. Four treatments with PFS of different size and location (100% rowcrop, 10% PFS of total watershed area at footslope, 10% PFS at footslope and in contour strips, 20% PFS at footslope and in contour strips) arranged in a balanced incomplete block design were seeded in July 2007. All watersheds were in bromegrass (Bromus L.) for at least 10 yr before treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
120
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 30 publications
5
120
0
Order By: Relevance
“…Schueler (1987) suggested that for adequate buffer infiltration, K sat values of soils should at least range from 69 to 127 mm h -1 . Overall low simulated buffer effectiveness by any type of buffer configuration, compared to reported values (82%; Helmers et al, 2012), may be attributed to low infiltration rates as a result of low K sat values of soils for both types of buffers: 16 to 32 mm h -1 and 1 to 13 mm h -1 in agroforestry and grass buffers, respectively (Seobi et al, 2005). Indeed, a recent experiment on claypan soils led to 19% to 28% buffer effectiveness for trapping herbicide loads with varying adsorption coefficients and for varying buffer widths (Lerch et al, 2017).…”
Section: Effectiveness Of Alternative Buffer Placementmentioning
confidence: 70%
See 2 more Smart Citations
“…Schueler (1987) suggested that for adequate buffer infiltration, K sat values of soils should at least range from 69 to 127 mm h -1 . Overall low simulated buffer effectiveness by any type of buffer configuration, compared to reported values (82%; Helmers et al, 2012), may be attributed to low infiltration rates as a result of low K sat values of soils for both types of buffers: 16 to 32 mm h -1 and 1 to 13 mm h -1 in agroforestry and grass buffers, respectively (Seobi et al, 2005). Indeed, a recent experiment on claypan soils led to 19% to 28% buffer effectiveness for trapping herbicide loads with varying adsorption coefficients and for varying buffer widths (Lerch et al, 2017).…”
Section: Effectiveness Of Alternative Buffer Placementmentioning
confidence: 70%
“…At field scale, effectiveness may be lower because of larger drainage area to buffer ratios and longer slope lengths, leading to increased concentrated flow (Helmers et al, 2008(Helmers et al, , 2012. In Iowa, a long-term replicated field experiment quantified the effectiveness of different combinations of edge-of-field and upland prairie buffers in 12 small watersheds (areas of 0.47 to 3.19 ha; Helmers et al, 2012;Zhou et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The estimate is that there are approximately 40 million acres of land within the Central US region that could be shifted from either row crop production or permanent pasture to production of perennial energy crops with net environmental benefits making agriculture more sustainable [49,53]. For example, research in Iowa has demonstrated that growing perennial vegetation in 10% of small watersheds where the remaining land was in crop production, reduced sediment loss by 90% and substantially reduced losses of P and N [22].…”
mentioning
confidence: 99%
“…Not only did prairie buffer strips increase catchment plant biodiversity without creating weed problems in adjacent cropped areas, they also reduced soil and nutrient loss from the crop catchments, provided habitat for a greater number of birds and insects, and were aesthetically pleasing (Liebman et al 2011, Cox 2012, Helmers et al 2012. Data from the experimental catchments in [2008][2009][2010] showed that catchments with buffer strips versus 100% crop catchments reduced water run-off by 40%, soil sediment loss by 96%, and N and phosphorus (P) losses in surface run-off by 82% and 86%, respectively (Helmers et al 2012, X. Zhou et al, Iowa State University, unpublished data).…”
Section: Discussionmentioning
confidence: 99%